2020
DOI: 10.3390/ijms21124395
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nano/Microparticles: Modification and Applications 2.0

Abstract: Currently, nano/microparticles are widely used in various fields [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 76 Studies have shown that coated and modified nanoparticles do not lose their original characteristics; however, by modifying the surface of the nanoparticles, the inherent toxicity of the nanoparticles could be reduced, and the biocompatibility of the nanoparticles could be improved at the same time. 77 , 78 The surface functionalization may enable further applications of nano silver in various fields.…”
Section: Promising Methods To Overcome Nano Silver-induced Cytotoxicitymentioning
confidence: 99%
“… 76 Studies have shown that coated and modified nanoparticles do not lose their original characteristics; however, by modifying the surface of the nanoparticles, the inherent toxicity of the nanoparticles could be reduced, and the biocompatibility of the nanoparticles could be improved at the same time. 77 , 78 The surface functionalization may enable further applications of nano silver in various fields.…”
Section: Promising Methods To Overcome Nano Silver-induced Cytotoxicitymentioning
confidence: 99%
“…Bacteria can survive in an air environment for several hours or even months, such as the Tuberculosis bacterium, Staphylococcus aureus, which will increase the risk of infection and disease. Silver nanomaterial has been one of the biggest nanotechnology successes since 1980 [1]. It can be applied in some medical fields, such as histopathological changes of organs (lungs, liver, kidney, and brain) using Agcoat nanosilver or biomedical applications on infection and inflammation [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, optimization of Pd-based alloys (such as alloying Pd with Ni, Co, Cu, Au, and Ag) and construction of novel metallic nanostructures have greatly enhanced their specific physical and chemical properties. [5][6][7][8] It is reported that Pd electronic characteristics can be tailored by the alloyed metals and the nanostructures morphologies. 9 The Pd electron regulation can not only optimize its binding energies to the reactive species and intermediates, but also improve its catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%